A digital promised land? Digital landscape as a heterotopia for disabled people in China. Issue 8 (2nd July 2020) - Lin, Zhongxuan; Yang, Liu
ABSTRACT: This article applies Foucault's concepts of heterotopia and governmentality to further explore the complexity of the relationship between disability and the digital landscape. To do so, we focus on the digital disability practices in China, where there are 85 million disabled people in residence. Based on ethnographic online participant observation, we explain why and how China's digital landscape serves as a heterotopia of disability governmentality through practices of 'conduct-of-conduct', 'counter-conduct', and 'self-conduct'. This qualitative research demonstrates why and how the Chinese government utilizes the digital landscape to govern disabled people, while the disabled people in the country resist this governance and attempt to self-govern. This study's results suggest three theoretical implications for future studies – a possible spatial turn in disability studies, a need in disability research to highlight the state's role, and a heterotopic imagination when researching disability and the digital landscape.